A high throughput ADC system for the PROMETEO test-bench of the ATLAS tile calorimeter - Spoor, Matthew (My University, 2020)
The Large Hadron Collider (LHC) is preparing for the High Luminosity upgrade (HL-LHC). The HL-LHC will give physicists the ability to probe new physics beyond the Standard Model (SM), examine electroweak symmetry in greater detail and to measure the properties of the Higgs boson and SM. During the Phase-II upgrade, the ATLAS Tile Calorimeter will need to undergo a complete redesign of its on and off-detector electronics. The PROMETEO (A Portable ReadOut ModulE for Tilecal ElectrOnics) stand-alone test-bench is under development to be used for the full certification of the new on-detector electronics of the TileCal. The test-bench has been designed to readout the digitised samples coming from the on-detector electronics to assess data quality in real-time and diagnose system malfunctions or errors. The system uses a Xilinx VC707 as amainboard with a QSFP+ FMC module for the readout and control of the TileCal electronics. Functions performed by PROMETEO are provided by multiple custom daughterboards: High Voltage Board, LED Driver Board and a 16 channel ADC board. The ADC board is used to digitise the analog signals used for Level 1 Trigger system coming from the TileCal on-detector adder boards at bunch crossing frequency. This dissertation presents a custom ADC trigger board I designed and produced for the PROMETEO test-bench of the ATLAS TileCal. This includes the physical hardware design and production as well as the firmware needed to manage and readout the board on the FPGA of the VC707
A thesis submitted in fulfilment of the requirements for the degree Master of Science in the Faculty of Science, University of the Witwatersrand, 2020